2017
DOI: 10.1177/0020764017691314
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of depression with cognitive insight and socio-occupational outcome in patients with schizophrenia

Abstract: Our results suggest that one-fourth of patients with schizophrenia have depression, compared to HDRS and PANSS-D, CDSS has highest concordance with clinician's diagnosis of depression and presence of depression is related to cognitive insight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Of note, some studies examining the relationship of clinical insight and depression in schizophrenia have failed to find significant relationships between these variables 86 . A metaanalysis of 50 cross-sectional studies found a weak relationship between clinical insight and depression, but reported that longitudinal studies suggested a stronger, more complex relationship which plays out differently depending upon the circumstances of the individual person's life 87 .…”
Section: Good Clinical Insight Is Associated With Depression and Poormentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, some studies examining the relationship of clinical insight and depression in schizophrenia have failed to find significant relationships between these variables 86 . A metaanalysis of 50 cross-sectional studies found a weak relationship between clinical insight and depression, but reported that longitudinal studies suggested a stronger, more complex relationship which plays out differently depending upon the circumstances of the individual person's life 87 .…”
Section: Good Clinical Insight Is Associated With Depression and Poormentioning
confidence: 99%
“…Greater levels of cognitive insight have also been linked to heightened levels of depression 77,86 , as well as lower levels of self-reported subjective recovery 89 and subjective quality of life 90 . Phelan et al 91 suggested a complex relationship in which higher self-certainty was linked to better interviewer-rated quality of life only when patients had greater levels of psychopathology.…”
Section: Good Cognitive Insight Is Associated With Depression and Poomentioning
confidence: 99%
“…The questionnaire algorithm allows to exclude the diagnosis during the interview and, therefore, depending on the answers obtained, it is not necessary to apply all the questions of the instrument. A study found that the kappa value of the Calgary Depression Scale for Schizophrenia (CDSS) and the of MDE module of the MINI indicated good concurrent validity, and the rates of depression in schizophrenia identified by these two scales were very similar (25% for the MINI and 23.5% for the CDSS, Grover et al, 2017). Also, a study points out that the MINI's reliability was (Henrique et al, 2004).…”
Section: Study Variables and Measuresmentioning
confidence: 99%
“…These differences in clinical assessment could at least in part account for our contrasting results compared with previous works. We suppose that the avolition dimension of the BNSS, as experiential domain of negative symptoms including avolition, anhedonia, and asociality, similarly to depression in other studies 45,46 , can support a self-evaluation of real-life functioning similar to the one provided by the caregiver. In other words, a higher degree of avolition could enhance a more "objective" perception of patients' limits of functioning.…”
Section: Discussionmentioning
confidence: 82%